Workplace Spirituality and Leadership Effectiveness Among Educational Managers in Malaysia. - Kanesan Abdullah, Abdul Ghani; Ismail, Aziah; Jamil Alzaidiyeen, Naser (2009)

(untitled)
The focus of this study was to investigate the relationship between the workplace spirituality and leadership effectiveness among secondary school principals in Malaysia. A quantitative technique (questionnaires) was used to collect data from 1510 teachers of secondary schools across the four States of Northern Peninsular Malaysia, namely, Penang, Kedah, Perlis and Northern Perak. The results of this study indicate that workplace spirituality has an important role to playas an aide to leadership development, as well as leadership effectiveness. The results also confirmed that effective leadership practices could explain significant variance in teachers' satisfaction and commitment as well as departmental performance. These findings are discussed in the light of currently available research literatures and both practical as well as theoretical implications of the study are highlighted. Future qualitative studies are needed to provide deeper insight.